Peran Negara Dalam Distribusi Kekayaan (Perspektif Ekonomi Islam) - Kuni Zakiyah (Institut Agama Islam Negeri (IAIN) Curup, 2017)
One of the most fundamental objectives of Islam is to bring happiness (Falah) for all Moslems both in the world and in the Hereafter and to realize the brotherhood among members of the Moslems community. This objective cannot be achieved if there are inequality and injustice in the distribution of wealth among society, the gap between the rich and the poor is still widening and there is class conflict/class struggle in society. In order to realize a fair distribution of wealth, fair and equitable, enforceable by means of the mechanisms of economic and non-economic mechanisms. Economic mechanism directed towards the productive sector, whereas non-economic mechanism, is not through productive economic activity, but through non-productive activities, for example, zakat, inheritance, and sodaqoh sunnah.